Inducing Performance in a Queue via Prices: The Case of a Riverine Port - Dasgupta, Ani; Ghosh, Madhubani (Management Science, 2000)
To optimize large-scale queuing systems configurations, OR professionals typically use discrete event simulation packages to examine in detail the movement of entities through such systems, assuming stochastic but fixed arrival patterns. Demand aspects are, however, routinely ignored as few attempts are made to capture the feedback effect of queue performance on the arrival process. Econometricians, on the other hand, use a simultaneous equations estimation approach relying on past data, but they typically disregard the technological insights provided by simulation. This paper combines both tools to study the ailing port system of Calcutta, India, and concludes that raising prices will improve both economic and engineering performances. Microeconomic models of shipowner behavior are constructed to explain the nature of the empirical findings. Finally, full-equilibrium demand elasticities are calculated using the dual prices from an appropriate nonlinear program, which are then compared to the benchmark value expected of profit-maximizing behavior.